Intracranial Dural Arteriovenous Fistulas with Retrograde Cortical Venous Drainage: Assessment with Cerebral Blood Volume by Dynamic Susceptibility Contrast Magnetic Resonance Imaging - Noguchi, K.; Kubo, M.; Kuwayama, N.; Kamisaki, Y.; Tomizawa, G.; Kameda, K.; Kawabe, H.; Ogawa, S.; Watanabe, N.; Endo, S.; Seto, H. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Retrograde cortical venous drainage (RCVD) is the most major risk factor for aggressive behavior of intracranial dural arteriovenous fistulas (DAVF). The purpose of this study was to assess the efficacy of relative cerebral blood volume (rCBV) map for RCVD in patients with DAVF.METHODS: Ten patients with angiographically proven DAVF with RCVD, 2 reference patients with DAVF without RCVD, and 10 control subjects underwent examinations with dynamic susceptibility contrast (DSC)-MR imaging. Four patients with DAVF with unilateral RCVD were evaluated, before and after treatment. The calculation of mean rCBV ratio was performed on a hemispheric basis. The mean rCBV ratio was defined as the value on one side (higher value side) divided by that on the other side (lower value side).RESULTS: In all patients with DAVF with RCVD, the rCBV map showed an increase in rCBV of the angiographically proved affected hemisphere. In 2 reference patients with DAVF without RCVD and all control subjects, the rCBV map showed no increase of rCBV. The mean rCBV ratio in patients with DAVF with RCVD was significantly higher than that of control subjects (P = .0002). Treatment response for RCVD was indicated by a decrease of CBV on the rCBV map and by a decrease of 22% in the mean rCBV ratio.CONCLUSIONS: Increased rCBV by DSC-MR correlated with RCVD in patients with DVAF. The assessment with rCBV for RCVD may be more quantitative than that with angiogram.